Parents' Interpersonal Communication Strategy To Minimize Media Exposure On Children - Sari, Elfira Maya (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The use of smartphone among children during covid 19 pandemic is increased. The overuse of smartphone could affect their mind set, emotion, and behaviour. This phenomenon issue parents to pay more attention on their children. The aim of the research is to describe parents’ interpersonal communication strategy in reducing the usage level of smartphone resulted less media exposure on children. The research method used were descriptive qualitative by conducting observation, interview, and documents. The research result shows children tend to be easily affected through attitude, character, and behaviour towards their parents. Expanding intensity of interaction with children is a great interpersonal communication strategy.